Changes in sprinting kinematics after an 8-week intervention mobility program and its relationship with maximal speed and acceleration in professional football players - Fleres, Luca (2020)
Sprinting is an essential skill in football, and it has been widely researched with special attention to linear trajectories. The mechanics of sprinting and the running technique are unique to each player, but there are anatomical and postural features that can have an impact on how a player runs, as is the case of lumbo-pelvic control and its positioning during sprinting. This study investigates whether pelvis positioning affects running mechanics and what changes might occur in the sprinting kinematics after an 8-week mobility intervention program aimed at optimizing lumbo-pelvic control. Ninety-five active professional football players playing in the highest league in Finland were included in this study. They performed 2 maximal 30m sprints as a baseline, and the measurements were repeated after 8 weeks. The players were given a mobility program and a series of progressive running drills after the first data collection point with the aim of increasing lumbo-pelvic control and improving running technique. The variables measured were top speed, horizontal force production, and kinematic analysis of the hip angles at touch down and toe-off. These two angles were then summed to create one single score, which will be referred to as the kickback score. This score represents the quality of the running technique. Top speed and acceleration were measured with Musclelab laser gun using split times at the 5m, 10m, 15m, 20m, 25m, and 30m marks. Kinematic analysis was performed using Kinovea motion analysis software. No statistically significant change (-0.98% +/- 5.14%, p = 0.06) was observed in the kickback score following the intervention. No statistically significant change was observed in top speed (0.06% +/- 2.84%, p = 0.97). There was a statistically significant change in horizontal force (F0), which increased by 2,20% +/- 6.64% (p = 0.01). No correlation was found between the three variables. This study demonstrated that 8 weeks of mobility and running technique protocols caused an increase in F0 even though no changes in running kinematics of professional footballers occurred. It also appears that changes in F0, top speed, and kickback mechanics are not associated with each other. Pelvis anterior rotation causes a decrease in hip flexion of up to 10 degrees, which has the kinematic consequence of creating a shorter path for vertical force production during sprinting. To the best of our knowledge, this study was the first to aim to induce changes in anatomical positioning and control of the pelvis and to investigate its impact on force production during full speed running. As a result of this study, some of the methods used for the kinematic analysis can be easily adopted by football coaches without requiring much expertise and used as a tool for individualized programs that aim at increasing running performance as well as injury prevention.